Whole Genome Sequencing of Lumpy Skin Disease Virus from 2021–2023 in Eastern Eurasia Reveals No More Recombination Signals in the Circulating Pool of Strains - Alexander Sprygin; Alena Krotova; Ma Jun; Olga Byadovskaya; Vladimir Kirpichenko; Jinchao Chen; Tserenchimed Sainnokhoi; Ilya Chvala (Viruses)
Having spanned thousands of kilometers from Africa through Europe, the Middle East, Central Asia through to the south eastern part of Eurasia in the recent decade, lumpy skin disease virus has now become entrenched in China, Thailand, Vietnam, and South Korea. In light of discovered findings on recombination, cluster 2.5 lineage strains are now dominant and continue to spread throughout Southeast Asia. To gain a better picture of the phylogenetic landscape in the field, whole genome sequencing of 11 LSDV isolates from Russia and Mongolia collected from 2021 to 2023 has been attempted to see the dynamics of recombination signals, as was shown for LSDV circulating in 2017–2019 in Russia and Kazakhstan. Deep sequencing performed direct from skin nodules along with data retrieved from Genbank provides the most recent update on molecular epidemiology of LSDV and demonstrates that no more mosaic variant of LSDV has been observed, and cluster 2.5 lineage is now the dominant lineage currently on the rise in the region with its own patterns of monophyletic evolution. These discoveries may help future investigations aimed at epidemiological surveillance and virus tracking in the context of currently identified lineages worldwide.